INCREASING THE FINANCIAL LITERACY OF MIGRANT WORKERS IN JAPAN THROUGH SHARIA FINANCIAL MANAGEMENT TRAINING - Rachmania Nurul Fitri Amijaya; Okyviandi Putra Erlangga; Mohammad Zeqi Yasin; Mohammad Nizar Anas (LP2M Universitas Ibrahimy, 2024)
The necessity for financial management skills among migrant workers was underscored by the prevalence of a family member engaging in overseas employment within Indonesian households. This was evident in the imperative role finance played in encouraging migrant employees to maximize their earnings beyond what they could achieve in Indonesia. In this study, the ABCD (asset-based community development) strategy was employed to empower the Japanese IPMI community, utilizing existing community assets for sustainable development. The Indonesian Muslim Nurses Association, a supportive network, facilitated mutual growth and the establishment of ukhuwah Islamiyyah, contributing to a robust community fabric. IPMI served as a pivotal venue for enhancing the community's financial literacy through various levels of community service. Before returning to Indonesia, migrant workers took proactive steps in financial planning, including saving for retirement and other financial goals. Migrant employees, upon joining IPMI, actively recorded costs, tracked income, and projected investments for pension funds through direct practice. This past-tense abstract emphasizes the crucial role of financial empowerment and community support in the journey of migrant workers. The result shows after this community service, many migrant workers aware about financial management and gained a deeper understanding of financial management principles, enabling them to make informed decisions regarding budgeting, saving, and investing.